Urban voids keeping a close grip on urban open spaces of QC Quadrangle - Antonio, Mayla L.
Continuous urban growth and sprawling city development in the outskirts of Metro Manila means less and less areas to develop and thus we are left with few open spaces. Unquestionably, open spaces contribute to the welfare of the human being, from being places of social interactions and rest, providing contact with nature, environmental benefits, and meeting sustainability goals are just few benefits that make living more meaningful in an urban setting. Urban open spaces are an essential part of urban development more than as an amenity, whether it is micro level - unit property or building projects, to meso level - subdivisions, mixed-use - developments, estate development or to macro level - CBDs, barangays or city. However, the concept of urban open space (UOS) is not well defined and understood in the practice and setting of urban development particularly in the macro level urban Metro Manila. This paper will establish the urban fabric concept, organize built spaces and urban open spaces (UOS), and further classify (UOS) in the large scale level. It will analyze existing laws and implementing regulations in practice, pertaining to planning of (UOS) specifically BP 220, PD 957 and PD 1216, through both qualitative and quantitative parameters. A method of assessing existing urban open spaces in a district level such as the QC Quadrangle will be developed in this research. The results of the study will enable a better understanding of UOS, which can have positive bearing on future studies, planning, development, and management of our urban areas. Keywords: urban open space, open space requirement, public spaces, BP 220, PD 957